The Application of Problem Bassed Learning to Improve Learning Motivation Skills, of Scientific Inquiry and Argumentation Skills of Students SMPN Kediri on the Material Changes and Environmental Pollutan - Reni Bekti Anila; Rofik Masruri; Febriana Irawati; Herry Cahya Kurniawan; Poppy Rahmatika Primandiri; Agus Muji Santoso (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aimed to measure the effectiveness of  problem based learning design study on the motivation skills, of inquiry and scientific argumentation skills. This is the type of study design non-equivalent control group design in class VII SMPN 1 Grogol Kediri on 12 up to 23 May 2015 on  the material changes and  environmental pollutan. Used some of the instruments to support research that motivation  questionnaire and inquiry skill rubric (process and product).  And rubric scientific argumentation skills are integrated in the cognitive achievement tes. Data tabulated later in the analysis using the program SPSS 16 for windows 2007. The study is showed that: 1) students motivation treatment group (80%) higher than the control group (70%); 2) inquiry skills of the control group with the treatment process is the same (α= 0,181>0,05) but the product of inquiry skills between the two group differed (α= 0,01<0,05); 3) ANACOVA test study showed that the skills of scientific argument between the treatment group and the control group is different (α=0,000<0,05). Concluded that the model of problem-based learning can increase learning motivation, skills of inquiry, the ability of the scientific arguments..Keywords: PBL, motivation to learn, skills of inquiry, scientific argumentation skills